2017
DOI: 10.1159/000481206
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Attenuates Kidney Protection by Angiotensin-Converting Enzyme Inhibition in Nondiabetic Chronic Kidney Disease

Abstract: Background: Cigarette smoking exacerbates the estimated glomerular filtration rate (eGFR) decline in nondiabetic chronic kidney disease (CKD) despite the kidney protection that is achieved by angiotensin converting enzyme inhibition (ACEI). Whether smoking cessation restores ACEI-related kidney protection is not known. Methods: This 5-year, prospective, prevention trial recruited 108 smokers and 108 nonsmokers with stage-2 nondiabetic CKD with primary hypertension and urine albumin-to-creatinine ratio (Ualb) >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…Earlier studies of a separate group of patients [26] suggested the need for 33 patients in each of the 3 groups to achieve 80% power and significance level of 0.05 to detect eGFR benefit of the interventions among the groups (assuming NaHCO 3 and F + V were equally effective in preserving eGFR) compared with UC. We identified individuals from our clinic system as described [27] who met these inclusion criteria: (1) nonmalignant hypertension; (2) eGFR by Modification of Diet in Renal Disease formula [28] = 30-59 mL/min/1.73 m 2 ; (3) PTCO 2 < 25 mM (the lower limit of normal in our clinical laboratory) and > 22 mM but < 24 mM upon follow-up measurement using ultrafluoremetry [29]; (4) macroalbuminuria because of the higher risk for subsequent GFR decline [30] than normoalbuminuria or microalbuminuria, so as to include participants at increased risk for nephropathy progression and thereby enhance our ability to detect an intervention effect on nephropathy progression; (5) able to tolerate angiotensin-converting enzyme inhibition (ACEI); (6) nonsmoking defined as not having smoked tobacco for ≥1 year prior to study because smoking is associated with exacerbation of hypertension-associated nephropathy [30][31][32]; (7) no diabetes or CVD on their problem lists and no clinical evidence of CVD; (8) ≥2 primary care physician visits in the preceding year, showing compliance with clinic visits; and (9) age ≥18 years and able to give consent. Exclusion criteria were (1) primary kidney disease or findings consistent thereof such as ≥3 red blood cells per highpowered field of urine or urine cellular casts; (2) history of diabetes or fasting blood glucose ≥110 mg/dL; (3) current pregnancy, history of malignances, chronic infections, or clinical evidence of CVD; (4) peripheral edema or diagnoses associated with edema such as heart/liver failure or nephrotic syndrome; (5) baseline plasma potassium concentration ([K + ]) > 4.6 mEq/L because observation of our cadre of such patients collected over many years and published studies [12,13] who agreed to randomization as outlined in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies of a separate group of patients [26] suggested the need for 33 patients in each of the 3 groups to achieve 80% power and significance level of 0.05 to detect eGFR benefit of the interventions among the groups (assuming NaHCO 3 and F + V were equally effective in preserving eGFR) compared with UC. We identified individuals from our clinic system as described [27] who met these inclusion criteria: (1) nonmalignant hypertension; (2) eGFR by Modification of Diet in Renal Disease formula [28] = 30-59 mL/min/1.73 m 2 ; (3) PTCO 2 < 25 mM (the lower limit of normal in our clinical laboratory) and > 22 mM but < 24 mM upon follow-up measurement using ultrafluoremetry [29]; (4) macroalbuminuria because of the higher risk for subsequent GFR decline [30] than normoalbuminuria or microalbuminuria, so as to include participants at increased risk for nephropathy progression and thereby enhance our ability to detect an intervention effect on nephropathy progression; (5) able to tolerate angiotensin-converting enzyme inhibition (ACEI); (6) nonsmoking defined as not having smoked tobacco for ≥1 year prior to study because smoking is associated with exacerbation of hypertension-associated nephropathy [30][31][32]; (7) no diabetes or CVD on their problem lists and no clinical evidence of CVD; (8) ≥2 primary care physician visits in the preceding year, showing compliance with clinic visits; and (9) age ≥18 years and able to give consent. Exclusion criteria were (1) primary kidney disease or findings consistent thereof such as ≥3 red blood cells per highpowered field of urine or urine cellular casts; (2) history of diabetes or fasting blood glucose ≥110 mg/dL; (3) current pregnancy, history of malignances, chronic infections, or clinical evidence of CVD; (4) peripheral edema or diagnoses associated with edema such as heart/liver failure or nephrotic syndrome; (5) baseline plasma potassium concentration ([K + ]) > 4.6 mEq/L because observation of our cadre of such patients collected over many years and published studies [12,13] who agreed to randomization as outlined in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies 20 suggested the need for 33 participants in each of the 3 groups to achieve 80% probability of seeing a P-value ,.05 difference of the HCO 3 2 and F 1 V groups in the primary outcome (assuming equal effectiveness of NaHCO 3 and F 1 V in preserving eGFR) compared with UC. We identified individuals from our clinic system as described 21 who met these inclusion criteria: (1) nonmalignant hypertension; (2) eGFR by Modification of Diet in Renal Disease formula 22 5 30-59 mL/min/ 1.73 m 2 ; (3) PTCO 2 , 25 mmol/L (the lower limit of normal in our clinical laboratory) and .22 mmol/L but ,24 mmol/L upon follow up measurement using ultrafluoremetry 23 ; (4) macroalbuminuria because of the higher risk for subsequent GFR decline 24 than normoalbuminuria or microalbuminuria; (5) able to tolerate angiotensinconverting enzyme inhibitor (ACEI); (6) non-smoking defined as not having smoked tobacco for $1 year prior to study entry because smoking is associated with exacerbation of hypertension-associated nephropathy [24][25][26] ; (7) no diabetes or CVD on their problem lists and no clinical evidence of CVD; (8) $2 primary care physician visits in the preceding year, showing compliance with clinic visits; and (9) age $ 18 years and able to give consent. Exclusion criteria were: (1) primary kidney disease or findings consistent thereof such as $3 red blood cells per high-powered field of urine or cellular casts; (2) history of diabetes or fasting blood glucose $110 mg/dL; (3) current pregnancy, history of malignances, chronic infections, or clinical evidence of CVD; (4) peripheral edema or diagnoses associated with edema such as heart/liver failure or nephrotic syndrome; (5) baseline plasma [K 1 ] .…”
mentioning
confidence: 99%
“…Angiontensin II is a hormone involved in blood pressure. Smoking decreases the ability of the body to protect against ACEI (Angiotensin-Converting Enzyme Inhibition), which leads to increased constriction of blood vessels (Roehm et al, 2017). It is involved in cognitive impairment and even brain injury (Mogi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%